2018
DOI: 10.1002/ppsc.201800237
|View full text |Cite
|
Sign up to set email alerts
|

Laser/Electron Irradiation on Indium Phosphide (InP) Semiconductor: Promising Pathways to In Situ Formation of Indium Nanoparticles

Abstract: In the current study, whether femtosecond laser and electron beam irradiation of indium phosphide (InP) are “green,” fast, and effective methods to produce metallic In nanoparticles is probed. High‐resolution transmission electron microscopy and energy‐dispersive X‐ray spectroscopy are employed to investigate the formation and growth of In nanoparticles on InP. Density functional theory and quantum theory of atoms in molecules calculations are employed to reveal the nature of formation of In nanoparticles unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The sample obtained in this procedure was referred to as the fs lAP. Although for comparison with the previous papers, a femtosecond laser was employed, further studies could be conducted in order to elucidate if it is possible the formation of metallic Ag by irradiation of pAP with other kind of lasers, as it happens in other Ag‐containing compounds …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample obtained in this procedure was referred to as the fs lAP. Although for comparison with the previous papers, a femtosecond laser was employed, further studies could be conducted in order to elucidate if it is possible the formation of metallic Ag by irradiation of pAP with other kind of lasers, as it happens in other Ag‐containing compounds …”
Section: Methodsmentioning
confidence: 99%
“…Our research group, using a joint combination of experimental and theoretical studies, has conducted studies for understanding the formation mechanism of Ag nanoparticles (NPs) provoked by the exposure to electron beams of an electronic microscope on the surfaces of several Ag‐based materials such as α‐Ag 2 WO 4 , β‐Ag 2 WO 4 , γ‐Ag 2 WO 4 , β‐Ag 2 MoO 4 , Ag 2 CrO 4 , AgVO 3 , Ag 2 V 2 O 7 , and Ag 3 PO 4 crystals . Furthermore, we have reported four new phenomena provoked by fs laser irradiation: i) the scale‐up of the formation of Ag NPs on α‐Ag 2 WO 4 with bactericidal properties; ii) the synthesis of metallic Bi NPs with coexisting crystallographic structures (rhombohedral, monoclinic, and cubic) on NaBiO 3 ; iii) the formation of In NPs on InP; and iv) the synthesis of Ag–Bi nanoalloys from inorganic oxide Ag 2 WO 4 and NaBiO 3 targets . Both fs and electron beam irradiation strategies allow us to obtain Ag NPs with interesting technological applications such as photoluminescent and bactericide materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is still a lack of efficient and easy synthesis to avoid these drawbacks and obtain well-crystallized materials. Very recently, we presented the scale-up of the formation of Ag nanoparticles on α-Ag 2 WO 4 with bactericidal properties via fs laser irradiation 81,82 and the formation of Bi and In nanoparticles on NaBiO 3 83 and InP 84,85 under fs irradiation, respectively. This procedure offers the ability to selectively tailor nanomaterials and, in the above cases, to promote properties such as photoluminescence (PL) emissions, with concomitant applications on photodegradation processes and antimicrobial activity.…”
mentioning
confidence: 99%
“…28,29 In this context, Bichoutskaia et al 30 summarized the experimental observations and analyzed the irradiation-induced processes in high-resolution TEM, while Knez et al proposed a computational scheme of the electron-beam-induced dynamics in metallic nanoclusters. 31 Our research group demonstrated that the EBI in TEM and/ or eld-emission scanning electron microscopy (FE-SEM) is a direct platform for the formation of Ag nanoparticles on the surfaces of different silver-based materials including Ag 2 WO 4 , 41,42 and NaBiO 3 , respectively. [43][44][45] The formation of these metal nanoparticles-semiconductor composites provided enhanced surface functionalities and paved the way for the development of materials with bactericidal/antibacterial, antifungal, and antitumor characteristics for use in clinical sterilization, and catalysts, which is crucial for the sustainable development of energy-related catalysis, environmental sustainability, ne chemical industry, and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%